Short-term risk and long-term incidence rate of infection and malignancy with IL-17 and IL-23 inhibitors in adult patients with psoriasis and psoriatic arthritis: a systematic review and meta-analysis - Wu, Shuwei; Xu, Yuanyuan; Yang, Lihua; Guo, Linghong; Jiang, Xian (Frontiers in Immunology, 2023)
The risk of infection and malignancy may be a concern for patients with psoriasis receiving interleukin (IL)-17 and IL-23 inhibitors, particularly with long-term treatments. We aimed to estimate the shortterm risks and long-term incidence rates of infection and malignancy with IL-17 or IL-23 antagonists in adult patients with psoriasis and psoriatic arthritis through this comprehensive meta-analysis (PROSPERO registration number: CRD42022363127). We searched PubMed, MEDLINE, Web of Science and ClinicalTrials.gov until May 17, 2023 for randomized placebo-controlled trials and longterm (≥ 52 weeks) open-label extension studies. The estimates of short-term risk ratios (RRs) and long-term exposure-adjusted incidence rates (EAIRs) were pooled using R software 4.1.1 and STATA 16.0. This review included 45 randomized placebo-controlled studies and 27 open-label extension studies. Short-term RRs of serious infection, overall infection and malignancy were 1.45 (95% confidence intervals,